Skolēnu pašvadītas mācīšanās prasmju veicināšana matemātikas mācībā 6.klasē - Beierbaha, Ivita (Latvijas Universitāte, 2021)
Pētījuma mērķis: pētīt skolēnu pašvadītas mācīšanās prasmju veicināšanu matemātikas mācībā un apkopot ieteikumus skolēnu pašvadītas mācīšanās prasmju veicināšanai matemātikas mācībā 6.klasē. Darbā analizēta pašvadīta mācīšanās prasme un pašvadītas mācīšanās prasmes veicināšanas metodes matemātikas mācībā. Veikts pētījums, kurā noskaidrots mācīšanās prasmju veicināšana matemātikas mācībā 6.klasē pēc izstrādātajām metodēm. Izstrādāti ieteikumi skolēnu pašvadītas mācīšanās prasmju veicināšanā matemātikas mācībā 6.klasē.

The aim of the research: to study the promotion of students self-directed learning skills in mathematics teaching and to compile recommendations for the promotion of students self-directed learning skills in mathematics teaching in 6th grade. The paper analyzes self-directed learning skills and methods of promoting self-directed learning skills in mathematics teaching. A study has been carried out to find out the promotion of learning skills in mathematics teaching in the 6th grade according to the developed methods. Recommendations have been developed for the promotion of students' self-directed learning skills in the teaching of mathematics in the 6th grade.
Promotion of students self-directed learning skills in mathematics teaching in 6th grade
Keywords: Skolas pedagoģija; Pašvadīta mācīšanās; prasme; Matemātika; skolēns